The Role of Widal, Typhidot and Tubex-TF Examinations in The Diagnosis of Typhoid Fever - Eirene Jaquelene K.Tomalata (Publikasi Indonesia, 2025)
Typhoid fever is a systemic infection caused by Salmonella enterica serovars Typhi and Paratyphi. This disease is transmitted through contaminated food or water and is endemic in many developing countries, including Indonesia. Timely and accurate diagnosis of typhoid fever is crucial for its management. Serological tests, such as the Widal test, Typhidot, and Tubex-TF, have become the primary methods for diagnosing typhoid fever. Each test has advantages and disadvantages, both in terms of sensitivity, specificity, and ease of use. The Widal test, although widely used, often cross-reacts with other bacterial infections and has varying degrees of sensitivity. Typhidot offers faster detection with high accuracy in the early stages of infection, but is still susceptible to cross-reactions. Meanwhile, Tubex-TF uses a semi-quantitative method that can provide results quickly, although interpretation of results can vary depending on the user's skills. Each of these serological testing methods should be selected based on clinical factors, laboratory facilities, and resource availability. This study aims to compare the three serological tests in the context of typhoid fever diagnosis in developing countries.